Neutrophil Extracellular Traps Form a Barrier between Necrotic and Viable Areas in Acute Abdominal Inflammation - Bilyy, Rostyslav; Fedorov, Volodymyr; Vovk, Volodymyr; Leppkes, Moritz; Dumych, Tetiana; Chopyak, Valentyna; Schett, Georg; Herrmann, Martin (Frontiers in Immunology, 2016)
Neutrophils form neutrophil extracellular traps (NETs) of decondensed DNA and histones that trap and immobilize particulate matter and microbial pathogens like bacteria. NET aggregates reportedly surround and isolate large objects like monosodium urate (MSU) crystals, which cannot be sufficiently cleared from tissues. In the setting of acute necrotizing pancreatitis massive tissue necrosis occurs, which is organized as pancreatic pseudocysts. In contrast to regular cysts, these pseudocysts are not surrounded by epithelial layers. We hypothesize that, instead, the necrotic areas observed in necrotizing pancreatitis are isolated from the surrounding healthy tissues by aggregated NETs. These may form an alternative, putatively transient barrier separating necrotic areas from viable tissue. To test this hypothesis, we investigated histological samples from the necropsy material of internal organs of two patients with necrotizing pancreatitis and peritonitis accompanied by multiple organ failure. Tissues including the inflammatory zone were stained with H&E and evaluated for signs of inflammation. Infiltrating neutrophils and NETs were detected by immunohistochemistry for DNA, neutrophil elastase, and citrullinated histone H3. Interestingly, in severely affected areas of pancreatic necrosis or peritonitis, chromatin stained positive for neutrophil elastase and citrullinated histone H3, and may, therefore, be considered NET-derived. These NET structures formed a layer which separated the necrotic core from the areas of viable tissue remains. A condensed layer of aggregated NETs thus spatially shields and isolates the site of necrosis, thereby limiting the spread of necrosis-associated proinflammatory mediators. We propose that necrotic debris may initiate and/or facilitate the formation of the NET-based surrogate barrier.